Vocational education of owners and SME employment growth: evidence from Israel. (2nd January 2021) - Gimmon, Eli; Farja, Yanay; Greenberg, Zeevik
ABSTRACT: OECD data show that in some countries the earnings of workers with tertiary vocational education are lower than those of workers with secondary education, in particular for the 25–34 years age group. Israel is one of those countries, and in this study we extend the analysis of this apparent anomaly using a quantitative methodology of multiple regression analysis and a survey of 699 SMEs through telephone interviews and a web-based questionnaire. We explored the employment growth rates of firms whose owners have secondary, academic and post-secondary vocational education. Findings show that compared to the base level of the owner's secondary education, the growth of businesses whose owners have academic education is higher, while vocational education of the owner is associated with lower growth. These findings can be explained by the specific skills acquired through vocational training which may not adequately fit the changing job market and business ecosystem.